The Dilemma of Belonging and the Burden of Englishness in Chinua Achebe’s No Longer at Ease - SAHED, Bachir; SERIR, Ilhem (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The present article examines the issue of cultural identity in Chinua Achebe’s No Longer at Ease (1960). The novel dramatizes Obi Okonkwo’s cultural displacement and identity (de)formation on the eve of Nigerian independence. Throughout the novel, Obi is described as being torn between the two worlds of African tradition and European modernity. Hence, the paper aims at highlighting Obi’s struggle to function properly within the emerging cultural forces of the 1950s in Nigeria. It scrutinises the anxiety of belonging in postcolonial African literature stressing ideas of displacement, alienation, and identity (de)formation. It endeavours to investigate Obi’s alienation and quest for identity in the light of Frantz Fanon’s ideas on identity and national culture as well as Homi Bhabha’s theories of hybridity. With a special focus on the work of Frantz Fanon, namely alienation and cultural stereotyping, as well as Homi Bhabha’s notion of Third Space, the article analyses the impact of the colonial culture on the protagonist. It maintains that Obi’s traditional Umuofian beliefs and his English education, combined with the aspects of life in the modern city of Lagos, create his cultural and linguistic ambivalence.